Inclusivity and the construction of memory in Mia Couto's 'Under the Frangipani' - Ngoveni, Lawrence (My University, 2007)
This research report examines Mia Couto’s novel Under the Frangipani as an intervention into the problematic of memory in post-war Mozambique. It attempts to locate Couto’s narratives among contemporary writing in Africa. It argues that Couto’s narratives combine allegory and magic realism in their endeavor to highlight the complexity of the Mozambican past and the need to include a diversity of voices from different sources. It focuses primarily on the novel’s inclusive narrative approach which manifests through the coexistence of putative worlds. In doing so, I explore the tension between the ontological assumptions of officialdom and those of the weak.
Lawrence Ngoveni, Student no 0204864A, MA thesis, Literature & Language Studies, Faculty of Humanities & Social Sciences. 2006. ngovenil@yahoo.com.
Keywords: inclusivity; memory; allegory; magical realism